Effects of a 12-hour neuromuscular electrical stimulation treatment program on the recovery of upper extremity function in sub-acute stroke patients: a randomized controlled pilot trial - Wang, Dao-Qing; Sun, Qiang-San; Liu, Ben-Ling; Cui, Bao-Juan; Zhang, Qi; Sun, Min; Qiu, Jian-Qing; Zeng, Fan-Shuo; Huang, Lai-Gang (Journal of Physical Therapy Science, 2015)
[Purpose] This study investigated the effects of a 12-hour neuromuscular electrical stimulation program in the evening hours on upper extremity function in sub-acute stroke patients. [Subjects and Methods] Forty-five subjects were randomized to one of three groups: 12-hour neuromuscular electrical stimulation group (n=15), which received 12 hours of neuromuscular electrical stimulation and conventional rehabilitation for the affected upper extremity; neuromuscular electrical stimulation group (n=15), which received 30 min of neuromuscular electrical stimulation and conventional rehabilitation; and control group (n=15), which received conventional rehabilitation only. The Fugl-Meyer assessment, Action Research Arm Test, and modified Ashworth scale were used to evaluate the effects before and after intervention, and 4 weeks later. [Results] The improvement in the distal (wrist-hand) components of the Fugl-Meyer assessment and Action Research Arm Test in the 12-hour neuromuscular electrical stimulation group was more significant than that in the neuromuscular electrical stimulation group. No significant difference was found between the two groups in the proximal component (shoulder-elbow) of the Fugl-Meyer assessment. [Conclusion] The 12-hour neuromuscular electrical stimulation group achieved better improvement in upper extremity motor function, especially in the wrist-hand function. This alternative therapeutic approach is easily applicable and can be used in stroke patients during rest or sleep.